2017
DOI: 10.1088/1361-6528/aa53c3
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of cobalt intercalation underneath epitaxial graphene on 6H-SiC(0 0 0 1)

Abstract: The intercalation behaviour of cobalt underneath both epitaxial graphene monolayer and bilayer on 6H-SiC(0001) have been investigated by scanning tunneling microscopy (STM) and density functional theory (DFT). Upon deposition, cobalt atoms prefer to agglomerate into clusters on the epitaxial graphene. After annealing the sample to 850 °C, the intercalation of the adsorbed cobalt atoms into both monolayer and bilayer epitaxial graphene on SiC takes place, as observed by the atomically resolved STM images. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
2
20
0
2
Order By: Relevance
“…Epitaxial graphene can readily accommodate intercalation. 14,15,18,19,39,40 However, intercalation through pristine, multilayer EG is limited by defects native to the grown graphene layers. Thus, the low defect density afforded by high-temperature EG synthesis techniques can limit the lateral scale of intercalation.…”
Section: Defect-mediated Intercalationmentioning
confidence: 99%
See 2 more Smart Citations
“…Epitaxial graphene can readily accommodate intercalation. 14,15,18,19,39,40 However, intercalation through pristine, multilayer EG is limited by defects native to the grown graphene layers. Thus, the low defect density afforded by high-temperature EG synthesis techniques can limit the lateral scale of intercalation.…”
Section: Defect-mediated Intercalationmentioning
confidence: 99%
“…19,27,34,40 Following this step, EG/SiC substrates are annealed at temperatures typically ≥600°C under ultra-high vacuum (UHV), to induce intercalation. 19,27,32,34,40 This synthesis approach is well suited to investigation of intercalated structures, due to the relative ease of characterizing samples in situ through LEED, ARPES, XPS, or a combination of all three techniques. Investigation of intercalated materials through scanning tunneling microscopy and spectroscopy is also common, and can reveal ordered intercalant structures underneath the graphene layers.…”
Section: Intercalation Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy required to activate each of these mechanisms is experimentally delivered by thermal annealing, and depends on the specific substrate onto which the Gr is grown and on the atomic species to be intercalated. DFT calculations indicate that the presence of a substrate lowers the energy barrier for the intercalation compared to free standing Gr, and that adatoms on top of Gr further reduce such barrier [22] [26].…”
Section: Thermally Activated Mechanisms For Co Intercalationmentioning
confidence: 99%
“…Metal intercalation under graphene on various substrates is by now common practice [1,2,3,4,5,6,7,8,9,10,11]. Indeed, it has been demonstrated that rare earth metals (RE = Nd, Sm, Dy, Er and Yb, and Eu, for example) deposited on graphene grown on SiC or Ir substrate can intercalate under the graphene lattice by annealing pre-deposited metals at elevated temperatures [1,4,9,12].…”
Section: Introductionmentioning
confidence: 99%